2015
DOI: 10.1002/jsfa.7368
|View full text |Cite
|
Sign up to set email alerts
|

Films based on protein isolated from croaker (Micropogonias furnieri) and palm oil

Abstract: The use of protein isolate obtained from fish residues of low commercial value and palm oil is viable for the production of biodegradable films because the latter constitute good barrier properties and thermal stability. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…That indicates greater evaporation of free water from the structure of the control film, which was also described by TONGNUANCHAN et al (2014), CARPINÉ et al (2015), and BATISTA (2016. The optimized film had higher hydrophobicity due to the addition of SA, which is corroborated by HALAL et al (2016).…”
Section: Filmssupporting
confidence: 55%
See 3 more Smart Citations
“…That indicates greater evaporation of free water from the structure of the control film, which was also described by TONGNUANCHAN et al (2014), CARPINÉ et al (2015), and BATISTA (2016. The optimized film had higher hydrophobicity due to the addition of SA, which is corroborated by HALAL et al (2016).…”
Section: Filmssupporting
confidence: 55%
“…ARAÚJO (2015) and ( 2016) found transmittance at the same wavelength of 78.73 to 87.97% and 75.2 to 87.6%, respectively, for fish myofibrillar protein films, i.e., slightly more transparent than the 11/13 films in this study. PIRES et al (2013) andHALAL et al (2016) also found lower transparency in fish protein films when oils were added. That can be due to the presence of lipid droplets dispersed in the film and the physical state of the lipid (solid) at room temperature (HALAL et al, 2016).…”
Section: Filmsmentioning
confidence: 92%
See 2 more Smart Citations
“…The better thermal stability was observed which might be due to interactions of polar groups present in the proteins side chains and wax fraction. [ 279 ] A recent study reported to enhance the thermal properties of gelatin‐based films using beeswax and carnauba wax and provided the same explanation. [ 280 ]…”
Section: Potential Use Of Lipids In Food Packaging Applicationsmentioning
confidence: 79%